Analisa Indeks Kinerja Pembelajaran Dosen Perguruan Tinggi Swasta Program Studi Sistem Informasi Di Kota Batam - Yvonne Wangdra (Computer Based Information System Journal, 2015)
Improved ability to manage and develop the college has been very necessary, including using the principles of modern management oriented to quality, one of which is to improve the performance of lecturers as a tip of the spear. For the owners and managers of universities, the quality management system is essentially nucleated on continuous improvements to strengthen and develop the quality of graduates that can be absorbed by the agencies and organizations. Samples in this research are year 150 Information System program college students in Batam city, who are on their second semester during the 2014-2015 academic year. The method used in this research to assess faculty performance index is Scales Rating. Based on this research method, there are similar patterns found on the respondent’s answers to all the problem statements, where respondents mostly agree with the statements provided.